2019
DOI: 10.15835/nbha47411641
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mycorrhiza Inoculation and Grafting for Sweet Pepper (Capsicum annuum L.) Crop Under Low-Tech Greenhouse Conditions

Abstract: In low-cost, unheated greenhouses and tunnels the use of arbuscular mycorrhizal fungi (AMF) and/or grafting can be a less expensive and sustainable solution to combat the adverse effects of monoculture, instead of costly soilless culture. The aim of the present study was to investigate the effects of a commercially available AMF inoculant and grafting on sweet pepper, under circumstances of modelling commercial low-tech greenhouse production. ‘SV9702PP F1’ sweet pepper hybrid was cultivated for seven months in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
1
4
1
2
Order By: Relevance
“…Moreover, similarly to the trial reported by Ombódi et al (2019), we observed a better yield response of pepper to mycorrhizal inoculation (+66% in the second fruit harvest made on 9 January-174 DAT) when the microclimate conditions for plant growth were suboptimal (low light and temperature occurring during January). Finally, in the current experiment the total yield increases induced by inoculation with AMF and Trichoderma koningii were due to both higher fruit number and mean fruit weight whereas in the trial of Ombódi et al (2019) the yield increases were mostly due to higher number of fruits. The above findings indicate a reduced activity of indigenous arbuscular mycorrhizal fungi and Trichoderma spp.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, similarly to the trial reported by Ombódi et al (2019), we observed a better yield response of pepper to mycorrhizal inoculation (+66% in the second fruit harvest made on 9 January-174 DAT) when the microclimate conditions for plant growth were suboptimal (low light and temperature occurring during January). Finally, in the current experiment the total yield increases induced by inoculation with AMF and Trichoderma koningii were due to both higher fruit number and mean fruit weight whereas in the trial of Ombódi et al (2019) the yield increases were mostly due to higher number of fruits. The above findings indicate a reduced activity of indigenous arbuscular mycorrhizal fungi and Trichoderma spp.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, in two field experiments, Ortas (2019) reported that mycorrhizal inoculation increased yield of the tomatoes, green peppers and eggplants and P and Zn uptake in comparison with uninoculated plants. In the current experiment the total yield increase resulting from inoculation of sweet pepper plants with AMF and Trichoderma koningi was higher (24%) than the value (18%) reported by Ombódi et al (2019) using an inoculum containing six different arbuscular mycorrhizal species under unheated greenhouse conditions and the value (12.7%) recorded by Almaca et al (2013) using an inoculum containing Glomus mosseae and G. etunicatum under field conditions. The above differences in pepper yield response could be attributed to the different mycorrhizal species used in the trials and the addition of Trichoderma koningi in the current experiment.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Disease‐suppressive soil is a promising tool in sustainable agriculture, which relies on the effective activation of indigenous microbial community to protect host plants against pathogens. Colonization by soil AM fungi is an important indicator for appraising plant nutrient acquisition, photosynthetic performance, and defense ability (Douds et al, 2012; Mathur et al, 2018; Ombodi et al, 2019). This study showed both decrease of root AM fungal colonization and increase of soil P. capsici population along with increasing severities of pepper Phytophthora blight (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The grafting technique is commonly used in horticultural crops of fruits, including solanaceous crops Chiomento et al (2020) Performance of the root system of tomato... (Ombódi et al, 2019), with the objective of improving plant tolerance to biotic (Lee, 2007) and abiotic stresses (Rouphael et al, 2017). The introduced plant (graft)…”
Section: The Substrate Cultivation Profile (Hydroponics)mentioning
confidence: 99%